Terrorism on the rise – What can WCA countries do to combat difficulties with international trade? - Neszmélyi, György Iván; Hrabovszki, Dorottya; Hrabovszki, Ágnes Zsuzsa (Afrika Tanulmányok / Hungarian Journal of African Studies, 2023)
In the last 5 years, the center of gravity of terrorism has shifted from the Middle East and North Africa (MENA) region to sub-Saharan Africa. As of 2018, this region had the highest number of fatalities and the greatest material damage. This paper assesses the situation of the countries most affected by terrorism in the WCA (West and Central-Africa) region by examining economic complexity, the costs of cross-border trade and corruption. The AEO (Authorized Economic Operator) program is a means of ensuring the security of international supply chains while simultaneously facilitating the cross-border flow of goods. By 2020, 97 countries in the world had operational AEO programs, but only one country in the WCO (World Customs Organization) WCA region had implemented one. The threat of terrorism is very high in seven countries of the region: Nigeria, Burkina Faso, Cameroon, Democratic Republic of Congo, Niger, Chad and Mali. As a result of the evaluation, it can be concluded that these countries need mechanisms to facilitate international trade and would benefit from the implementation of the AEO program.